2023
DOI: 10.2147/ndt.s407731
|View full text |Cite
|
Sign up to set email alerts
|

The Synaptic and Circuit Functions of Vitamin D in Neurodevelopment Disorders

Abstract: Vitamin D deficiency/insufficiency is a public health issue around the world. According to epidemiological studies, low vitamin D levels have been associated with an increased risk of some neurodevelopmental disorders, including autism spectrum disorder (ASD) and attention-deficit hyperactivity disorder (ADHD). Animal models reveal that vitamin D has a variety of impacts on the synapses and circuits in the brain. A lack of vitamin D affects the expression of synaptic proteins, as well as the synthesis and meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 185 publications
0
3
0
Order By: Relevance
“…Vitamin D deficiency has been linked to various NDDs and psychiatric disorders, including ADHD, ASD, and schizophrenia [ 65 67 ]. Individuals with ADHD and ASD frequently exhibit lower levels of 25-hydroxyvitamin D (25(OH)D) in their serum compared to their healthy counterparts [ 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D deficiency has been linked to various NDDs and psychiatric disorders, including ADHD, ASD, and schizophrenia [ 65 67 ]. Individuals with ADHD and ASD frequently exhibit lower levels of 25-hydroxyvitamin D (25(OH)D) in their serum compared to their healthy counterparts [ 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is uncertainty around the definition of vitamin D insufficiency or deficiency, 74 particularly for neurodevelopment, 14 as well as lack of clearly defined underlying mechanisms through which vitamin D influences neurodevelopment. [12][13][14][15][16][17][18][19][20][21][22] Even the most recent Cochrane review of vitamin D in pregnancy identified 30 trials in over 7000 women (without reporting child neurodevelopment) and found the quality of evidence to be moderate to very low. 75 Future studies should focus on sufficiently large (powered) samples of vitamin D-deficient populations to verify that low vitamin D in pregnancy does not pose a threat to child neurodevelopment.…”
Section: Discussionmentioning
confidence: 99%
“…11 Some evidence from observational animal and human studies suggests a role of vitamin D for neurodevelopment and functioning, although findings are inconclusive and specific underlying mechanisms driving the association are not well established. [12][13][14][15][16][17][18][19][20][21][22] A number of cohort and case-control studies have reported associations between low vitamin D in pregnancy and/or childhood and increased risk of behaviour problems such as Autism Spectrum Disorder and Attention Deficit Hyperactivity. [23][24][25][26][27] Two reviews of trials of vitamin D supplementation for children with attention-deficit/hyperactivity disorder also found a small decrease in symptoms, although authors noted the quality of evidence was low.…”
mentioning
confidence: 99%
“…As mentioned earlier, gut microbiota also plays a role in gut GABA production and maintenance of normal gut GABA levels. Nutritional support of the GABAergic system with GABA or GABA receptor ligands, food, and vitamins has been suggested as treatment options for neurodevelopmental and aging-related disorders associated with GABAergic dysfunction [32][33][34]. Vitamin D deficiency is known to induce an E/I imbalance and supplementation has been reported to recover impairments of the GABAergic system [33,35].…”
Section: Introductionmentioning
confidence: 99%
“…Nutritional support of the GABAergic system with GABA or GABA receptor ligands, food, and vitamins has been suggested as treatment options for neurodevelopmental and aging-related disorders associated with GABAergic dysfunction [32][33][34]. Vitamin D deficiency is known to induce an E/I imbalance and supplementation has been reported to recover impairments of the GABAergic system [33,35]. These findings highlight the importance of diet in maintaining healthy brain function and the opportunity for nutritional support to correct the E/I imbalance.…”
Section: Introductionmentioning
confidence: 99%